Pós-estruturalismo e pós-anarquismo: conexões - Vieira Júnior, Roberto (2012)
The Post-structuralism has occupied a prominent place among the political theories that aim to explain and analyze the political relations of the post-modern world, not only for the richness of its concepts but also for the depth of their analyzes. In the same field of political theory, another "school" theoretical search space and gaining recognition in academic space: postanarchism. This dissertation aims to analyze and compare poststructuralism and post-anarchism seeks to identify and point out elements that connect both. To achieve this goal, this paper uses discursive corpus as the works of Ernesto Laclau, Jacques Rancière, Saul Newman and Lewis Call to analyze the meanings given by these authors for categories such as freedom, equality, and subject, as well as identify the influences of each building one of these directions